ICO as a financing method : Legal status at the interface of investment–based and rewards–based crowdfunding - Kauppi, Niko (Helsinki Law Review, 2020)
An Initial Coin Offering (ICO) is a blockchain-based financing method that can be described as a hybrid form of crowdfunding as it contains characteristics of both crowdfunding and IPOs. The first ICO took place in 2013 but still, after tens of billions of dollars have been raised, the phenomenon is surrounded by legal uncertainty. This article aims to highlight the issues relevant to the evaluation of ICOs at the interface of investment-based and rewards-based crowdfunding. This interface has become important with the emergence of ICOs, as blockchain technology allows the issuance and speculative trading of different types of digital assets, such as utility tokens and security tokens. The evaluation is largely based on the European concept of a transferable security as defined in the Markets in Financial Instruments Directive 2014/65/EU (MiFID II). The main conclusion of this article is that the issuance of tokens with attached dividend-like profit rights (i.e. security tokens) closely resembles the issuance of transferable securities and therefore financial laws should apply to security token issuances. Due to the possibility of speculative trading on secondary markets, questions relating to investor protection arise also in connection to tokens without attached profit rights (i.e. utility tokens). However, applying existing financial laws to utility token offerings would not provide the means for adequate investor protection due to the special characteristics of ICOs.